A step-by-step preparation method of a pure graphite negative electrode high-voltage gel lithium battery
Patent Information
- Application Number
- CN202611021645.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-09-15
Smart Images

Figure CN122762845A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of gel electrolyte battery technology, and in particular to a stepwise preparation method for a pure graphite negative electrode high-voltage gel lithium battery. Background Technology
[0002] As the core power source for modern electronic devices, electric vehicles, and energy storage systems, improving the energy density of lithium-ion batteries has always been a key direction for industry development. Increasing the charging cut-off voltage of cathode materials, especially lithium cobalt oxide, is one effective way to increase battery specific capacity. In existing gel lithium battery manufacturing processes, in-situ polymerization technology is typically used to form a polymer gel network inside the cell to fix the liquid electrolyte, aiming to improve the interface contact between the electrode and the electrolyte and reduce the risk of leakage. Conventional production processes generally include electrode assembly, vacuum drying, one-time or stepwise electrolyte injection, constant-temperature wetting, heating polymerization, formation, and aging. In these existing technical solutions, each process is usually executed sequentially according to a preset fixed time, fixed temperature, and fixed injection volume. After the previous process is completed, it automatically flows to the next process. The entire production process mainly relies on the static setting of process parameters to control the quality of the final product.
[0003] However, in existing technologies, due to objective differences in raw material batches, electrode pore structures, and environmental humidity among different battery cells, fixed process parameters are difficult to adapt to the actual state of each cell. If subsequent processes, such as drying or impregnation, do not achieve the expected results, the resulting deviations will be directly carried over to the subsequent polymerization and high-voltage formation stages, leading to phenomena such as localized liquid shortages, uneven gel distribution, unstable interfacial films, and even gas swelling in some cells. Furthermore, the lack of real-time detection and dynamic adjustment mechanisms for abnormal states affects the batch consistency and yield of high-voltage gel lithium batteries. Summary of the Invention
[0004] This application provides a stepwise preparation method for pure graphite negative electrode high-voltage gel lithium battery to solve the above problems. The method includes: S1. The battery cell is assembled using a high-voltage positive electrode sheet, a pure graphite negative electrode sheet, and a porous diaphragm, and the battery cell is dried, injected with liquid in stages, and impregnated. S2. Obtain the wetting state parameters of the battery cell, and determine whether the battery cell meets the polymerization admission conditions based on the wetting state parameters. Only the battery cells that meet the polymerization admission conditions are subjected to prepolymerization, deep polymerization and cooling and standing to obtain gel battery cells. S3. Obtain the gel state parameters of the gel cell, determine whether the gel cell meets the activation admission conditions based on the gel state parameters, and only perform interface activation on the gel cells that meet the activation admission conditions. S4. Obtain the activation state parameters after interface activation, and determine whether the gel cell meets the formation admission conditions based on the activation state parameters. Only perform the first formation on the gel cells that meet the formation admission conditions. The cutoff voltage of the first formation is lower than the target high voltage cutoff voltage. S5. Perform interface buffering on the gel cell that has completed the first formation, obtain the interface state parameters after the first formation, determine whether the gel cell meets the high voltage access conditions based on the interface state parameters, and only perform target high voltage formation on the gel cell that meets the high voltage access conditions. The charging cutoff voltage of the target high voltage formation is not lower than 4.45V. S6. Aging the gel cell that has completed the target high-voltage formation, and determining the finished cell based on the state changes before and after aging. The wetting state parameter is used to characterize the degree of wetting of the electrolyte into the electrode pores and membrane channels; the gel state parameter is used to characterize the impedance and structural stability after polymerization; the activation state parameter is used to characterize the interfacial conductivity between the gel and the electrode; and the interface state parameter is used to characterize the stability of the electrode interface formed after the first formation.
[0005] Optionally, the positive electrode active material of the high-voltage positive electrode sheet is high-voltage lithium cobalt oxide suitable for a charging cutoff voltage of not less than 4.45V; the negative electrode active material of the pure graphite negative electrode sheet is artificial graphite, natural graphite, or a combination of the two, and the negative electrode active material does not contain silicon, silicon suboxide, silicon-carbon composite materials, or tin-based negative electrode materials.
[0006] Optionally, the battery cell is dried, including: The battery cell is pre-dried at 80–110°C for 4–12 hours. The pre-dried battery cells were subjected to deep vacuum drying for 12–60 hours at 105–130℃ and a vacuum degree not exceeding -0.095 MPa. The internal moisture content of the battery cell after deep vacuum drying is detected, and the battery cell is injected with electrolyte in stages when the internal moisture content is not higher than 100 ppm.
[0007] Optionally, the stepwise injection and wetting include: Determine the saturated liquid absorption capacity of the battery cell; A first electrolyte is injected into the battery cell. The first electrolyte includes a base high-voltage electrolyte, a polymer monomer, and an initiator. The amount of the first electrolyte injected is 60% to 85% of the saturated absorbent volume. The battery cell injected with the first electrolyte was vacuum-immersed for 30 to 120 minutes at 35–55°C and a vacuum degree not higher than -0.090 MPa. A second electrolyte is injected into the vacuum-impregnated cell. The second electrolyte is either a basic high-voltage electrolyte or an electrolyte with a lower content of polymer monomers than the first electrolyte. The amount of the second electrolyte injected is 15% to 40% of the saturated liquid absorption capacity. After the second injection of electrolyte is completed, let the battery cell stand for 5 to 60 minutes.
[0008] Optionally, the wetting state parameters include the total weight gain of the battery cell, the pressure change at the end of the vacuum wetting period, the AC internal resistance before and after wetting, and the AC internal resistance change rate during the standing process after the second liquid injection. The aggregation admission conditions include: The total increase in the weight of the battery cell is within the target total injection volume range of the first electrolyte and the second electrolyte; The pressure change between two adjacent detection cycles at the end of the vacuum immersion period shall not exceed the upper limit of the pressure change. The internal resistance of AC after immersion is lower than that at the initial stage of immersion. The rate of change of AC internal resistance during the settling process does not exceed the upper limit of the rate of change of internal resistance.
[0009] Optionally, the prepolymerization, deep polymerization, and cooling and settling include: The battery cell is prepolymerized at 50–65°C for 1–4 hours; Deep polymerization is carried out by heating to 65-80℃ at a heating rate of 0.5-3℃ / min. The temperature of deep polymerization is 5-20℃ higher than the temperature of prepolymerization. The deeply polymerized battery cells are cooled to 20-30°C at a cooling rate of 2-10°C / h and left to stand for 0.5-6 hours. The gel state parameters include AC internal resistance, open circuit voltage, and cell thickness at the beginning and end of the settling period. The activation admission conditions include that the AC internal resistance at the end of the settling period is not higher than the upper limit of the gel internal resistance, the AC internal resistance change rate during the settling process is not higher than the upper limit of the gel internal resistance change rate, the open circuit voltage change is not higher than the upper limit of the voltage change, and the cell thickness change is not higher than the upper limit of the thickness change.
[0010] Optionally, the interface activation includes a first interface activation and a second interface activation; The first interface is activated at 25–35°C with a current of 0.02C–0.08C for 0.5–3 hours. When the AC internal resistance after the first interface activation is lower than the AC internal resistance before the first interface activation, and the maximum temperature rise and cell thickness change during the first interface activation process are not higher than the corresponding upper limits, the second interface activation is performed. The second interface activation is carried out at 32-40°C with a current of 0.06C-0.12C, and the temperature and current of the second interface activation are higher than those of the first interface activation, respectively. After the second interface activation is completed, the cell is left to stand for 5 to 60 minutes. The activation state parameters include the voltage drop before and after standing, the change in AC internal resistance before and after the second interface activation, the maximum temperature rise during the interface activation process, and the change in cell thickness.
[0011] Optionally, the first formation is performed at 35–45°C with a current of 0.08C–0.20C, and the cutoff voltage of the first formation is 4.15–4.35V; The interface buffering includes stopping charging after the first formation is completed and letting it stand at 35-45°C for 10-120 minutes. The interface state parameters include the voltage drop during the interface buffering process, the change in AC internal resistance before and after the first formation, the change in cell thickness, and the cell temperature recovery time. The high-voltage access conditions include that the voltage drop, AC internal resistance change, and cell thickness change are not higher than their respective upper limits, and the cell temperature recovers to the target temperature range within a set recovery time. The target high voltage formation is carried out at 40-50°C with a current of 0.10C-0.30C to 4.45-4.55V, and after reaching the target high voltage cutoff voltage, constant voltage charging is performed until the charging current drops to 0.01C-0.05C.
[0012] Optionally, if the state parameters at any stage do not meet the corresponding admission conditions, the following procedure shall be followed: When the total increase in cell weight is less than the target total electrolyte injection volume, replenish electrolyte; When the total weight gain of the battery cell is within the target total liquid injection volume range, but the AC internal resistance after immersion is higher than the upper limit of the immersion internal resistance, extend the vacuum immersion time or perform alternating immersion under vacuum and normal pressure. When the polymerization conversion rate of the gel cell is lower than the lower limit of conversion rate, supplementary polymerization is carried out; when the AC internal resistance of the gel cell is higher than the upper limit of gel internal resistance and the change in cell thickness is not higher than the corresponding upper limit, hot soaking and standing are carried out at 35-50℃. When the maximum temperature rise or cell thickness change during the interface activation process exceeds the corresponding upper limit, reduce the interface activation current or suspend charging. When the voltage drop after the first formation is higher than the corresponding upper limit, while the change in AC internal resistance and the change in cell thickness are not higher than the corresponding upper limit, the interface buffer time is extended, or a current lower than the first formation current is used for supplementary film formation. If the battery cell produces gas, or if either the maximum temperature rise or the thickness change exceeds the upper limit for anomaly detection, the battery cell will be stopped from proceeding to the next manufacturing stage.
[0013] Optionally, the aging process includes placing the gel cell that has completed the target high-voltage formation at 35–50°C for 12–48 hours. The changes in state before and after aging include the decrease in open-circuit voltage, the increase in AC internal resistance, the increase in cell thickness, and self-discharge parameters. When the open-circuit voltage drop, AC internal resistance growth rate, and cell thickness growth rate are not higher than the corresponding finished product judgment upper limit, and the cell does not bulge, leak, or produce gas, the cell is determined to be a finished cell. When the cell does not exhibit bulging, leakage, or gas generation, but the AC internal resistance growth rate or open-circuit voltage drop exceeds the corresponding finished product judgment limit, the state change is obtained again after extending the aging time.
[0014] Through the above technical solution, this application achieves the following effects: This application obtains parameters that reflect the actual state of the battery cell at each stage, including drying, wetting, in-situ polymerization, interface activation, first formation, target high-voltage formation, and aging. Based on the corresponding admission conditions, it determines whether the battery cell should enter the next preparation stage. This avoids relying solely on fixed time, fixed temperature, and fixed current for process flow, and can promptly identify and block the transmission of deviations from previous processes to subsequent high-voltage stages, thereby improving the controllability of the preparation process.
[0015] This application combines step-by-step drying, step-by-step liquid injection, and vacuum impregnation, and uses the cell weight gain, pressure changes, and AC internal resistance changes to determine the electrolyte impregnation state. This allows the first electrolyte containing polymeric monomers to fully enter the electrode pores and diaphragm channels. The remaining liquid absorption space is then replenished by the second electrolyte, reducing local liquid shortages, unwetted areas, and local polymer agglomeration. This is beneficial for forming a continuous and uniform gel network and improving the cell's ion transport performance.
[0016] This application employs an in-situ polymerization method that combines prepolymerization, deep polymerization, controlled cooling, and static setting. After polymerization, activation access is determined based on gel state parameters such as AC internal resistance, open-circuit voltage, and cell thickness. This method can stabilize the polymerization reaction before electrochemical activation, reduce abnormal temperature rise, thickness fluctuations, and increased interfacial impedance caused by the overlap of residual thermal polymerization and interfacial activation processes, and improve the stability of the gel structure and electrode interface.
[0017] This application employs a two-stage interface activation method that gradually transitions from low temperature and low current to higher temperature and current. The activation process is controlled based on the decrease in internal resistance, temperature rise, thickness change, and voltage drop after standing. This allows a stable ion-conducting interface to be gradually established between the gel electrolyte and the pure graphite negative electrode and high-voltage positive electrode, reducing local polarization and side reactions caused by direct activation with higher current, and facilitating the formation of a continuous and stable electrode interface film.
[0018] This application first performs a first formation under conditions lower than the target high-voltage cutoff voltage, then releases polarization through an interface buffer, and makes a high-voltage access judgment based on the voltage drop, change in AC internal resistance, change in cell thickness, and temperature recovery time, allowing only cells with stable interface states to enter the target high-voltage formation. This avoids the cell directly switching from a low-voltage stage to a high-voltage stage, reducing the risks of instantaneous expansion, gas generation, and interface film damage during the high-voltage formation process, and improving the high-voltage storage stability and capacity retention capability of pure graphite anode cells at higher charging cutoff voltages.
[0019] This application addresses various issues that may arise at different stages, such as insufficient liquid injection, inadequate wetting, high internal resistance after polymerization, abnormal activation temperature rise, and excessive voltage drop after the first formation. It proposes corrective paths including supplementary liquid injection, extended or alternating wetting, supplementary polymerization, hot wetting and settling, reduced activation current, extended interface buffer, and low-current supplementary film formation. These corrective paths allow cells that have temporarily deviated from the target state but are still repairable to continue operating after passing retesting. Simultaneously, cells that are unrecoverable or have safety abnormalities are promptly removed, thereby reducing the scrap of repairable intermediates and improving manufacturing yield and material utilization.
[0020] This application establishes a closed-loop manufacturing process that integrates multiple stages of state detection, access control, anomaly correction, and aging determination. This process can reduce the impact of differences in raw material batches, electrode pore structure, and environmental conditions on product performance, reduce thickness growth and AC internal resistance dispersion between cells, and improve the consistency, yield, and safety of cells in the same batch. It is suitable for the preparation of gel lithium batteries composed of pure graphite anode and high-voltage cathode. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a flowchart of a stepwise preparation method for a pure graphite negative electrode high-voltage gel lithium battery according to this application; Figure 2SEM morphology comparison of gel distribution in the cross-section of the battery cell electrode sheet for the experimental group and the control group, provided in the embodiments of this application; Figure 3 Comparison of SEM morphology of the negative electrode surface film after 100 cycles for the experimental group and the control group provided in this application embodiment; Figure 4 The graphs showing the increase in cell thickness over time during the high-voltage formation stage for the experimental and control groups provided in this application embodiment. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0024] Furthermore, the term "and / or" in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character " / " in this article, unless otherwise specified, generally indicates that the preceding and following related objects have an "or" relationship.
[0025] The embodiments of this application will now be described in further detail with reference to the accompanying drawings.
[0026] Example 1 This embodiment verifies the feasibility of a stepped preparation method for a pure graphite negative electrode high-voltage gel lithium battery under standard conditions and the performance of the resulting cell. Unless otherwise stated, this embodiment and subsequent embodiments use stacked soft-pack cells with a rated capacity of 1.0Ah and dimensions of 70mm×45mm×5.0mm. Five parallel cells are set in each group, and the test results are taken as the arithmetic mean. The AC internal resistance is tested using a 1kHz AC internal resistance tester at 25±1℃ with a disturbance current of 10mA; the open circuit voltage is measured using a six-and-a-half-digit digital voltmeter; the cell thickness is measured at five locations (center and four corners) under a constant compression pressure of 5kPa at 25±1℃, and the average value is taken; the temperature is collected at 1s intervals using a thermocouple attached to the center of the large surface of the cell. The moisture content is determined by disassembling the cells in the same batch under an environment with a dew point not higher than -50℃, and then using the Karl Fischer method to detect the moisture content of the positive electrode, negative electrode, and separator, and calculating it by weighted average.
[0027] (1) Cell assembly: The positive electrode active material is high-voltage monocrystalline lithium cobalt oxide with an average particle size D50 of 12.6 μm and an aluminum oxide coating layer on the surface. The mass ratio of lithium cobalt oxide, conductive carbon black and polyvinylidene fluoride in the positive electrode slurry is 96.5:2.0:1.5. Using N-methylpyrrolidone as solvent, after coating, drying at 120℃ and rolling, a positive electrode sheet with a compaction density of 3.90 g / cm³ and a single-sided surface capacity of 4.10 mAh / cm² is obtained. The negative electrode active material is artificial graphite with an average particle size D50 of 15.2 μm. The mass ratio of artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber in the negative electrode slurry is 95.8:1.2:1.5:1.5. Using deionized water as the dispersion medium, the material is coated, dried at 100℃, and rolled to obtain a pure graphite negative electrode sheet with a compaction density of 1.65 g / cm³. The negative electrode active material does not contain silicon, silicon suboxide, silicon-carbon composite materials, or tin-based materials. The positive / negative electrode capacity ratio (N / P) is 1.08. The separator is a PE-based membrane with a thickness of 9 μm and a porosity of 40%. Stacking, tab welding, and aluminum-plastic film pre-sealing are completed in a dry environment with a dew point not exceeding -45℃ to obtain the soft-pack battery cell to be dried.
[0028] (2) Step drying: The cells to be dried were first pre-dried at 95℃ for 8 hours, then heated to 120℃ at a rate of 1℃ / min, and deep vacuum dried for 48 hours under a vacuum degree not exceeding -0.098MPa. During the deep drying period, drying nitrogen was introduced to atmospheric pressure every 12 hours and vacuum was drawn again to promote the removal of moisture from the electrode pores. After drying, the temperature was lowered to below 45℃ while maintaining vacuum. The internal moisture content of the cells in the same batch was measured to be 75ppm. The production cells were weighed every 1 hour, and the mass change rates for two consecutive testing cycles were 0.008% and 0.006%, respectively, both lower than 0.02% / h. After the vacuum valve was closed, the pressure change was recorded within 5 minutes, and the pressure recovery rate was 4.2Pa / min, lower than 5Pa / min. Therefore, it was determined that this batch of cells met the liquid injection access conditions of moisture content not exceeding 100ppm, continuous mass change rate not exceeding 0.02% / h, and vacuum pressure recovery rate not exceeding 5Pa / min.
[0029] (3) Stepwise electrolyte injection and wetting: The basic high-voltage electrolyte was prepared by dissolving 1.1 mol / L LiPF6 in a mixed solvent of ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate in a volume ratio of 20:50:30, and adding 1.0% vinylene carbonate, 1.0% lithium difluorooxalate borate, and 0.5% tris(trimethylsilyl)phosphate according to the total mass of the basic high-voltage electrolyte. Its water content was less than 20 ppm. The electrolyte was injected stepwise in increments of 0.20 g using the same type of test cells. After each injection, the cells were wetting for 20 min at 45°C and a vacuum degree not exceeding -0.095 MPa. The maximum injected mass that the cell could retain without free liquid precipitation was taken as the saturated liquid absorption. The average saturated liquid absorption of the three test cells was 3.50 ± 0.04 g. In this embodiment, 2.625g of the first electrolyte is first injected. The first electrolyte contains 88.0% basic high-voltage electrolyte, 11.0% PEGDA600, 0.8% AIBN and 0.2% MEHQ by total mass. The electrolyte is then vacuum-immersed at 45°C and a vacuum degree not exceeding -0.095MPa for 60 minutes. Subsequently, 0.875g of the second electrolyte, which is the aforementioned basic high-voltage electrolyte, is injected and the electrolyte is allowed to stand at 25°C for 20 minutes. The actual total weight gain was 3.48±0.03g, which is within ±2% of the target total injection volume of 3.50g. The pressure changes in two adjacent 5-minute monitoring cycles at the end of the vacuum impregnation period were 8Pa and 6Pa, respectively. The AC internal resistance decreased from 31.6±0.8mΩ at the beginning of injection to 17.4±0.6mΩ, a decrease of 44.9%. After the second injection, the AC internal resistance at the beginning and end of the standing period were 17.6±0.6mΩ and 17.4±0.6mΩ, respectively, with a conversion rate of 0.57% / h. The above results meet the polymerization access conditions of a total weight gain deviation of no more than ±2%, a pressure change of no more than 10Pa / 5min, an AC internal resistance decrease rate of no less than 20% after impregnation, and a standing internal resistance change rate of no more than 1% / h.
[0030] (4) In-situ polymerization: The impregnated battery cell was finally sealed and placed in a constant temperature chamber with a flat clamping plate, and the battery cell was kept flat with a clamping pressure of 5 kPa. Prepolymerization was carried out at 60℃ for 2 h, followed by deep polymerization at 2℃ / min to 70℃ for 4 h, and then cooling to 25℃ at 5℃ / h and standing for 2 h. Using a test sample prepared in the same batch as the electrolyte in the battery cell and heated synchronously, the residual polymerization heat release was determined by differential scanning calorimetry and the monomer conversion rate was calculated. The polymerization conversion rate was found to be 93.6±1.2%, which is higher than the lower limit of 90% conversion rate. The AC internal resistance of the cell at the beginning and end of the cooling and settling period was 20.2±0.7mΩ and 19.8±0.6mΩ, respectively, with a change rate of 1.98%, which is lower than the upper limit of 3% for gel internal resistance change rate. At the end of the settling period, the AC internal resistance was lower than the upper limit of 23.0mΩ for gel internal resistance. The open-circuit voltage changed from 3.286V to 3.283V, a change of 3mV. The average thickness change was 7μm. These indicators are lower than the upper limits of 5mV for voltage change and 10μm for thickness change, respectively, indicating that the obtained gel cell meets the activation admission conditions.
[0031] (5) Interface Activation: The first interface was activated at 30℃ with a current of 0.05C (50mA) for 1 hour, with a cumulative charging capacity of 50mAh. The AC internal resistance before and after the first interface activation was 19.8±0.6mΩ and 16.8±0.5mΩ, respectively, a decrease of 15.2%. The maximum temperature rise during the activation process was 2.6℃, and the average thickness change was 4μm, which were lower than the conversion upper limits of 3℃ and 5μm, respectively, so the second interface activation was initiated. The second interface was activated at 35℃ with a current of 0.08C (80mA) for 1 hour, with a cumulative charging capacity of 80mAh. After the activation, the interface was left to stand at 35℃ for 30 minutes. The voltage before and after the stand was 3.812V and 3.796V, respectively, a voltage drop of 16mV. The AC internal resistance change before and after the second interface activation was 0.6mΩ. The maximum temperature rise during both activation processes was 3.4℃, and the cumulative thickness change was 7μm. The above data meet the formation access conditions of voltage drop not exceeding 25mV, AC internal resistance increase not exceeding 1.5mΩ, maximum temperature rise not exceeding 5℃, and thickness change not exceeding 12μm.
[0032] (6) Stepped Formation: The cell is charged at 0.10C (100mA) at 40℃ to 4.30V to complete the first formation, with a cumulative charge capacity of 612±8mAh. Charging is stopped and the cell is left to stand at 40℃ for 40 minutes for interface buffering. The voltage is 4.300V when charging is stopped and 4.272V when standing is finished, with a voltage drop of 28mV. The increase in AC internal resistance before and after the first formation is 1.1mΩ; the average thickness change is 15μm; and the cell surface temperature recovers to 40±1℃ within 18 minutes. The above indicators meet the high-voltage access conditions of voltage drop not exceeding 35mV, increase in AC internal resistance not exceeding 2.0mΩ, thickness change not exceeding 20μm, and temperature recovery to the target temperature range within 30 minutes. Subsequently, it was charged at 0.15C (150mA) at 45℃ to 4.53V, and then charged at 4.53V at a constant voltage for 105±6 minutes until the current dropped to 0.02C (20mA), completing the target high-voltage formation. Temperature and thickness were continuously monitored during the formation process, with a maximum temperature rise of 4.1℃, and no abnormal sudden rise or bulging was observed.
[0033] (7) Aging Judgment: After the target high-voltage formation is completed, the open-circuit voltage, AC internal resistance, and thickness before aging are recorded. After aging at 45℃ for 24 hours, the results are tested again. The open-circuit voltage before and after aging are 4.528V and 4.511V, respectively, a decrease of 17mV; the AC internal resistance is 18.3mΩ and 18.9mΩ, respectively, an increase of 3.28%; the average thickness increases by 32μm; and the self-discharge parameter calculated based on the ratio of the decrease in open-circuit voltage to the aging time is 0.71mV / h. The above results are lower than the upper limits for finished product judgment of 30mV, 5%, 80μm, and 1.25mV / h, respectively. No bulging, leakage, or continuous gas production was found through visual inspection and underwater volume inspection. Therefore, this batch of cells is judged as finished cells.
[0034] The prepared gel-gel battery cell had a smooth appearance, intact sealing edges, and no leakage. The first charge-discharge test was conducted at 25℃: charging to 4.53V at 0.2C and maintaining a constant voltage to 0.02C, followed by discharging to 3.0V at 0.2C. The initial charge capacity was 1016±11mAh, the initial discharge capacity was 909±10mAh, and the initial charge-discharge coulombic efficiency was 89.5±0.4%. After storing the fully charged 4.53V cell at 60±2℃ for 7 days, the average thickness increase was 1.20±0.18%, the AC internal resistance increase was 3.50±0.42%, and the capacity retention after returning to 25℃ and discharging at 0.2C was 96.8±0.6%.
[0035] This embodiment demonstrates that in a pure graphite negative electrode and a high-voltage positive electrode system of not less than 4.45V, by sequentially setting drying, wetting, gel stabilization, interface activation, interface stabilization after the first formation, and high-voltage formation access conditions, it is possible to determine whether to enter the next stage at each stage based on detectable state parameters, thereby obtaining a finished battery cell with sufficient wetting, stable gel structure, and controllable high-voltage interface state.
[0036] Example 2 This embodiment aims to verify the impact of moisture content nearing its upper limit during the drying stage on subsequent processes and performance. The same cell materials, assembly methods, testing methods, and finished product evaluation criteria as in Example 1 were used, with five parallel cells in each group.
[0037] Under the same preparation conditions as in Example 1, the deep vacuum drying time was shortened from 48 h to 36 h. The internal moisture content measured by the same batch of test cells was 98 ± 1 ppm, close to the upper limit of 100 ppm for liquid injection. The mass change rates of the produced cells in two consecutive 1-hour testing cycles were 0.015% and 0.013%, respectively, and the vacuum pressure recovery rate was 4.8 Pa / min, both meeting the liquid injection requirements. The actual total weight gain after stepwise liquid injection was 3.49 ± 0.04 g, the AC internal resistance after wetting was 18.1 ± 0.7 mΩ, the AC internal resistance at the end of the polymerization settling period was 20.5 ± 0.7 mΩ, the open-circuit voltage change was 4 mV, and the thickness change was 8 μm. The voltage drop at the interface buffer after the first formation was 31 mV, all of which did not exceed the corresponding upper limit described in Example 1. The remaining polymerization, activation, formation, and aging steps were performed according to Example 1.
[0038] All cells in this batch passed the acceptance criteria at each stage. After 24 hours of aging, the open-circuit voltage drop was 20±2mV, the AC internal resistance increase rate was 3.9±0.5%, and the thickness increase was 38±6μm. After 7 days of high-voltage storage at 4.53V and 60±2℃, the average thickness increase rate was 1.50±0.21%, the AC internal resistance increase rate was 4.20±0.51%, and the capacity retention rate was 95.9±0.7%. The changes in thickness and internal resistance were slightly higher than in Example 1, but still within the range for finished product judgment and high-voltage storage evaluation.
[0039] The results show that when the internal moisture content of the battery cell is close to the upper limit of 100 ppm, as long as the quality stability and pressure recovery rate simultaneously meet the liquid injection access conditions, and the state parameter judgment is continued in the subsequent stages, in-situ polymerization, interface activation and high-pressure formation can still be completed, indicating that the limit of moisture content not exceeding 100 ppm is feasible.
[0040] Example 3 This embodiment aims to verify the effect of the first electrolyte injection volume being at the lower limit in stepwise electrolyte injection on the wetting effect. The same cell materials and testing conditions as in Example 1 were used, with 5 parallel cells set up in each group.
[0041] Keeping other conditions unchanged in Example 1, the injection volume of the first electrolyte was adjusted from 75% to 60% of the saturated absorbent volume, i.e., 2.10g of the first electrolyte was injected, and the injection volume of the second electrolyte was adjusted to 40%, i.e., 1.40g of the second electrolyte was injected. The first vacuum impregnation was still carried out at 45°C and a vacuum degree not higher than -0.095MPa. After 60 minutes of impregnation, the AC internal resistance of the cell was 23.8±0.9mΩ, which was only 24.7% lower than the initial injection. Moreover, the internal resistance change rate in the first 20 minutes after the second injection was 1.42% / h, which did not meet the polymerization admission condition of a static internal resistance change rate not higher than 1% / h set in this example.
[0042] Based on the wetting parameters, the vacuum wetting time was extended by 30 min to a total of 90 min, and the cell was allowed to stand for another 20 min after the second injection. The actual total weight gain was measured to be 3.47 ± 0.04 g. The pressure changes in the two adjacent 5-min cycles at the end of the vacuum wetting period were 9 Pa and 7 Pa, respectively. The AC internal resistance decreased to 20.6 ± 0.7 mΩ, and the rate of change of internal resistance after the second injection and standing period decreased to 0.82% / h, meeting the polymerization access conditions. Subsequent steps were performed according to Example 1. At the end of the polymerization standing period, the AC internal resistance was 21.1 ± 0.6 mΩ, and the voltage drop after the first formation was 30 mV. The thickness growth rate of the obtained cell after storage at 4.53 V and 60 ± 2 °C for 7 days was 1.40 ± 0.19%, and the AC internal resistance growth rate was 3.9 ± 0.4%.
[0043] The results show that when the first electrolyte injection amount is 60% of the saturated absorption amount, insufficient wetting can be identified by using the change rate of AC internal resistance and static internal resistance. Based on this, the vacuum wetting time can be extended from 60 min to 90 min, which can allow the electrolyte to further enter the electrode pores and diaphragm channels. This proves that the injection ratio range of 60% to 85% of the first electrolyte can be implemented in conjunction with state detection.
[0044] Example 4 This embodiment aims to verify the effect of the prepolymerization temperature at its upper limit on gel network formation. The same battery cells, first electrolyte, and second electrolyte as in Example 1 were used, with five parallel battery cells in each group.
[0045] After the polymerization access conditions were met under the immersion state, the prepolymerization temperature was adjusted from 60℃ to 65℃, and the prepolymerization time was shortened from 2h to 1.5h. Subsequently, the temperature was increased to 70℃ at 2℃ / min and deep polymerized for 4h, then cooled to 25℃ at 5℃ / h and allowed to stand for 2h, while other conditions remained unchanged. The polymerization conversion rate of the simultaneously tested sample was 94.2±1.0%, and the gel fraction of the gel sample after extraction with dimethyl carbonate for 24h and vacuum drying was 91.8±1.3%, with no visible local blocky aggregation observed.
[0046] The AC internal resistance at the beginning and end of the cell cooling and settling period were 20.7±0.7mΩ and 20.1±0.6mΩ, respectively, with the AC internal resistance below 23.0mΩ at the end of the settling period. The open-circuit voltage change was 4mV, and the average thickness change was 8μm, both meeting the activation access conditions. Subsequently, interface activation, step formation, and aging were completed according to Example 1. After 7 days of high-voltage storage at 4.53V and 60±2℃, the thickness growth rate was 1.30±0.17%, the AC internal resistance growth rate was 3.7±0.4%, and the capacity retention rate was 96.4±0.6%.
[0047] The results show that even after increasing the prepolymerization temperature to 65℃ and shortening the prepolymerization time accordingly, gel cells that meet the requirements for conversion rate, internal resistance stability, open-circuit voltage, and thickness variation can still be obtained, indicating that the prepolymerization temperature range of 50-65℃ is feasible.
[0048] Example 5 This embodiment aims to verify the effect of the first interface activation current being at its lower limit on interface conduction. The same gel cell as in Example 1 was used, with five parallel cells in each group.
[0049] During the interface activation stage, the first interface activation current was adjusted from 0.05C to 0.02C, i.e., 20mA, and the activation time was extended from 1h to 2.5h to maintain the cumulative charging capacity at 50mAh; the first interface activation temperature was maintained at 30℃. Before activation, the AC internal resistance was 19.9±0.6mΩ, and after 0.5h, 1.5h, and 2.5h activation, it was 19.1±0.6mΩ, 17.8±0.5mΩ, and 17.0±0.5mΩ, respectively, showing a continuous decreasing trend.
[0050] At the end of the first interface activation, the AC internal resistance decreased by 14.6% compared to before activation, the maximum temperature rise was 1.4℃, and the average thickness change was 3μm, meeting the conditions for entering the second interface activation. Subsequently, the second interface activation was carried out at 35℃ and 0.08C according to Example 1, and the cell was left to stand for 30 minutes, with a voltage drop of 15mV. After storage at 4.53V and 60±2℃ for 7 days, the AC internal resistance increased by 3.20±0.38%, and the thickness increased by 1.18±0.16%.
[0051] The results show that by using a lower limit current of 0.02C and extending the activation time of the first interface, the temperature rise and thickness fluctuation during the activation process can be reduced while maintaining the cumulative activation charge, and the AC internal resistance can be continuously reduced. This indicates that the activation current range of 0.02C to 0.08C for the first interface can achieve gradual conduction of the gel-electrode interface.
[0052] Example 6 This embodiment aims to verify the impact of the first formation cutoff voltage being at its upper limit on the high-voltage access judgment. The same gel cells as in Example 1 are used, with 5 parallel cells in each group.
[0053] The first formation was carried out at 40°C with a constant current of 0.10C, increasing the cutoff voltage from 4.30V to 4.35V, and the cumulative charging capacity was 648±9mAh. After reaching 4.35V, charging was stopped and the mixture was left to stand at 40°C for 40 minutes for interface buffering. The remaining polymerization, activation and target high-voltage formation conditions were the same as in Example 1.
[0054] The voltage was 4.350V when charging stopped and 4.317V at the end of resting, with a voltage drop of 33mV, which is lower than the high-voltage access limit of 35mV. The increase in AC internal resistance before and after the first formation was 1.4mΩ, the average thickness change was 18μm, and the surface temperature recovered to 40±1℃ within 22 minutes, all meeting the high-voltage access conditions. Subsequently, it was charged to 4.53V at 0.15C and kept constant at 0.02C. No swelling or leakage was found after aging. After 7 days of storage at 4.53V and 60±2℃, the thickness growth rate was 1.36±0.20%, the AC internal resistance growth rate was 4.0±0.5%, and the capacity retention rate was 96.1±0.6%.
[0055] The results show that when the first formation cutoff voltage is increased to 4.35V, the voltage drop after interface buffering increases. However, by combining the voltage drop, internal resistance, thickness and temperature recovery time, cells that can enter the target high-voltage formation can still be screened, indicating that the first formation cutoff voltage range of 4.15 to 4.35V is feasible.
[0056] Example 7 This embodiment verifies the correction path for insufficiently wetted cells. The same cell system and testing method as in Example 1 are used, with 5 parallel cells set in each group.
[0057] After the initial injection of 2.625g of the first electrolyte, the solution was immersed for 20 minutes at 45℃ and a vacuum level not exceeding -0.095MPa to create an under-wetting state. Subsequently, 0.875g of the second electrolyte was injected and allowed to stand for 20 minutes. The total weight gain was measured to be 3.48±0.03g, within the target range. However, the AC internal resistance was 27.8±1.0mΩ, exceeding the wetting internal resistance control value of 22.0mΩ, and the internal resistance change rate during standing was 1.36% / h. Therefore, polymerization was not permitted. For correction, three vacuum-atmospheric pressure alternating cycles were performed at 45℃. Each cycle was maintained at a pressure not exceeding -0.095MPa for 5 minutes, followed by the introduction of dry nitrogen to restore atmospheric pressure and maintenance for another 5 minutes. The total correction time was 30 minutes. After correction, the solution was allowed to stand at 25℃ for 20 minutes for homogenization. The AC internal resistance was reduced to 21.1±0.7mΩ, the pressure change at the end was 8Pa / 5min, and the static internal resistance change rate was 0.70% / h, all of which met the polymerization access conditions. Subsequently, polymerization, activation, formation and aging were completed according to Example 1.
[0058] After correction, the AC internal resistance at the end of the polymerization settling period was 21.4 ± 0.7 mΩ, and the voltage drop after the first formation was 30 mV, both meeting the subsequent access conditions. The thickness increase rate after 7 days of high-pressure storage at 4.53 V and 60 ± 2 °C was 1.30 ± 0.18%, and the AC internal resistance increase rate was 3.8 ± 0.4%, similar to that of Example 1. If the AC internal resistance is still higher than 22.0 mΩ or leakage occurs after two rounds of alternating vacuum-atmospheric pressure impregnation, the cell will be rejected and will not proceed to the polymerization stage.
[0059] This embodiment demonstrates that when the total injection volume is qualified but the AC internal resistance and static change rate indicate that the electrolyte has not fully entered the pores, the state parameters can be restored to the polymerization acceptance range by alternating vacuum-atmospheric pressure wetting and static liquid homogenization, thereby avoiding the solidification of insufficient wetting defects in the gel network.
[0060] Example 8 This embodiment verifies the correction path for cells with high AC internal resistance after polymerization. The same liquid injection, polymerization, and testing methods as in Example 1 are used, with 5 parallel cells set up in each group.
[0061] After polymerization, cooling, and standing for 2 hours, the cell open-circuit voltage change was measured to be 4 mV and the average thickness change to be 7 μm, both within the corresponding upper limits. However, at the end of the standing period, the AC internal resistance was 25.6 ± 0.8 mΩ, exceeding the upper limit of 23.0 mΩ for gel internal resistance. Therefore, direct interface activation was not permitted. The cell was then hot-immersed at 40°C and left to stand for 2 hours, then cooled to 30°C at a rate of 1°C / min and left to stand for 30 minutes. The AC internal resistance was then measured again and reduced to 22.4 ± 0.7 mΩ. The internal resistance change rates for the two consecutive 30-minute monitoring cycles were 1.2% and 0.8%, respectively, finally meeting the activation criteria of AC internal resistance not exceeding 23.0 mΩ and change rate not exceeding 3%. Subsequently, the first interface was activated at 30°C with 0.03°C (30mA) for 2 hours. The AC internal resistance before and after the first interface activation was 22.4±0.7mΩ and 18.6±0.6mΩ, respectively, a decrease of 17.0%. The maximum temperature rise was 1.9°C, and the thickness change was 4μm. After the conversion conditions were met, the second interface was activated according to Example 1.
[0062] After hot soaking and low-current first interface activation, the voltage drop after 30 minutes of standing following the second interface activation was 18mV, and the AC internal resistance change was 0.8mΩ, meeting the formation acceptance conditions. The cell ultimately achieved the target high-voltage formation at 4.53V. The AC internal resistance growth rate after aging was 4.1±0.5%, and the thickness growth rate after 7 days of storage at 4.53V and 60±2℃ was 1.42±0.20%, with no bulging or leakage observed.
[0063] This embodiment demonstrates that when the open-circuit voltage and thickness are stable after polymerization but the AC internal resistance is high, hot wetting is first used to further redistribute the liquid phase retained in the gel, and low-current activation is only performed after the AC internal resistance recovers to the activation threshold range. This can improve the conduction state of the gel-electrode interface while maintaining the control logic of "not proceeding to the next stage if the threshold condition is not met".
[0064] Example 9 This embodiment verifies the correction path when the interface state after the first formation does not meet the high-voltage access conditions. The same cell system as in Embodiment 1 is used, with 5 parallel cells in each group.
[0065] The battery cell was processed according to Example 1 up to the first formation stage. After charging to 4.30V at 40°C and 0.10C, it was left to stand for 30 minutes. The voltage was 4.300V when charging stopped, and 4.258V after 30 minutes of standing, with a voltage drop of 42mV, which is higher than the high voltage access limit of 35mV. However, the increase in AC internal resistance before and after the first formation was 1.3mΩ, the average thickness change was 16μm, and the maximum temperature rise was 3.8°C, all of which did not exceed the corresponding upper limit, indicating that the anomaly was mainly due to insufficient release of interface polarization. The interface buffer time was extended by 30 minutes to a total of 60 minutes, and a supplementary charge of 50mA (0.05C, lower than the first formation current) was applied for 30 minutes to bring the cumulative charge to 25mAh. After the supplementary film formation, it was again left to stand at 40°C for 30 minutes. The voltage drop during retesting was 29mV, the increase in AC internal resistance was 1.5mΩ, the thickness change was 17μm, and the temperature recovered to 40±1℃ within 20 minutes. After meeting the high-voltage access conditions, it entered the 4.53V target high-voltage formation.
[0066] After extended buffering and supplementary film formation, the cell completes the target high-voltage formation and aging. After 7 days of storage at 4.53V and 60±2℃, the capacity retention rate is 96.2±0.7%, the thickness increase rate is 1.38±0.19%, and the AC internal resistance increase rate is 4.0±0.5%. If the voltage drop after supplementary film formation and subsequent resting is still higher than 35mV, or if the thickness change exceeds 20μm, the maximum temperature rise exceeds the abnormal upper limit, or gas production continues, then the high-voltage formation of the cell is stopped.
[0067] This embodiment demonstrates that when the internal resistance, thickness, and temperature rise after the first formation are not abnormal, but the voltage drop exceeds the limit on its own, the interface polarization can be further released and restored to the high voltage access range by extending the interface buffer and using a lower current to supplement the film formation. Cells that still do not meet the standards after correction are screened out, thereby avoiding the unstable interface from directly bearing the target high voltage.
[0068] Example 10 This embodiment compares the impact of a fixed process and the stepped fabrication process of this application on batch consistency. Fifty cells assembled from the same batch of positive electrode, negative electrode, and separator were selected and randomly divided into an experimental group and a control group, with 25 cells in each group.
[0069] The experimental group adopted the stepwise preparation method of Example 1, detecting state parameters at each stage and performing corresponding corrections or screenings on cells that did not meet the admission criteria. The control group used the same fixed parameters as Example 1: 95℃ pre-drying for 8 hours, 120℃ vacuum drying for 48 hours, stepwise electrolyte injection of 75% first electrolyte and 25% second electrolyte, 45℃ vacuum impregnation for 60 minutes, 60℃ pre-polymerization for 2 hours, 70℃ deep polymerization for 4 hours, two-stage activation at 30℃ and 35℃, charging to 4.30V at 40℃, and charging to 4.53V at 45℃. However, the flow was not determined based on moisture, AC internal resistance, pressure, thickness, voltage drop, or temperature rise; all cells entered the next stage at a fixed time. Both groups were aged at 45℃ for 24 hours and stored at 60±2℃ for 7 days after being fully charged to 4.53V. The number of abnormal cells with a thickness growth rate exceeding 3%, the average AC internal resistance growth rate, and the number of finished products were statistically analyzed.
[0070] The specific test results are shown in Table 1. The average thickness growth rate of the experimental group was 1.35% ± 0.62%, while that of the control group was 2.76% ± 1.48%. Only 24 samples in the experimental group met the evaluation requirements for finished products and high-pressure storage, while only 17 samples in the control group met the same requirements.
[0071] Table 1 Comparison of high-voltage storage performance of battery cells under different manufacturing processes Experimental group (stepwise preparation) 25 1 3.6±1.1 The average thickness growth rate was 1.35% ± 0.62%, with 24 finished products. Control group (fixed process) 25 8 6.8±2.4 The average thickness growth rate was 2.76% ± 1.48%, with 17 finished products. As shown in Table 1, only one cell in the experimental group using the stepped fabrication method had a thickness growth rate exceeding 3%, while eight cells in the fixed-process control group had a growth rate exceeding 3%. The average AC internal resistance growth rate of the experimental group was 3.6%, significantly lower than the 6.8% of the control group. The experimental group was able to identify and correct cells exhibiting edge states after impregnation, polymerization, or the first formation before entering the next stage, indicating that state parameter admission control reduced the probability of preceding deviations being carried into the high-voltage stage and improved the consistency of cells in the same batch.
[0072] Example 11 This embodiment aims to verify the effect of the wetting threshold on gel distribution and localized fluid deficiency. Twelve cells assembled in the same batch were randomly divided into an experimental group and a control group, with six cells in each group.
[0073] The experimental group followed Example 1, performing vacuum wetting with the first electrolyte, replenishment with the second electrolyte, and wetting status monitoring. In-situ polymerization was only carried out after the total weight gain, pressure change, AC internal resistance decrease rate, and static internal resistance change rate all met the polymerization threshold. The control group was only allowed to stand at 25°C for 10 minutes after the first electrolyte was injected, followed by the injection of the second electrolyte and direct polymerization without vacuum wetting or wetting status assessment. Both groups used the same polymerization, activation, formation, and aging conditions. After the first charge-discharge cycle, three cells from each group were discharged to 3.0V and disassembled in an environment with a dew point not exceeding -50°C. Samples were taken from the center of the electrode, 10 mm from the tab end, and 10 mm from the sealing edge. Ten SEM fields were observed at each location, and image analysis software was used to calculate the proportion of the area continuously covered by the gel to the observed area. The remaining three cells from each group were used for rate performance testing.
[0074] like Figure 2 As shown, the gel network in the cross-section of the electrode in the experimental group was continuously distributed along the electrode pores, with an average continuous gel coverage rate of 93.1% ± 2.4%. The average continuous gel coverage rate in the control group was 78.6% ± 5.7%, with localized areas and blocky aggregates not covered by continuous gel observed near the tab end and the edge of the electrode. Rate testing was conducted at 25℃, charging to 4.53V at 0.2C and maintaining a constant voltage to 0.02C, followed by discharge to 3.0V at 0.2C and 2C respectively. The ratio of the 2C discharge capacity to the 0.2C discharge capacity was used as the 2C capacity retention rate. The 2C capacity retention rate in the experimental group was 92.0% ± 1.3%, while that in the control group was 85.0% ± 2.1%.
[0075] Figure 2 The quantitative results above indicate that the wetting threshold can identify cells where the electrolyte has not yet fully entered the electrode pores before polymerization, reducing the possibility of unwetted areas being prematurely closed by the polymerization network, thereby improving the continuity of gel distribution and rate discharge capability.
[0076] Example 12 This embodiment aims to verify the influence of gel stability threshold on the uniformity of interfacial film formation. Twelve cells assembled in the same batch were randomly divided into an experimental group and a control group, with six cells in each group.
[0077] The experimental group, following Example 1, cooled to 25°C at a rate of 5°C / h after deep polymerization and allowed to stand for 2 hours. AC internal resistance, open-circuit voltage, and thickness were measured. Interface activation was performed only after the activation threshold was met. The control group, after deep polymerization at 70°C for 4 hours, only cooled to 35°C and allowed to stand for 10 minutes. No gel state detection was performed before direct first interface activation at 0.05°C. The maximum temperature rise and thickness change during the activation process were recorded for both groups. Both groups were subsequently charged at 25°C to 4.53V at 0.5C, kept constant at 0.05C, and then discharged at 0.5C to 3.0V for 100 cycles. After cycling, electrochemical impedance spectroscopy (EIS) was performed at 50% charge, with a frequency range of 100kHz–10mHz and a perturbation voltage of 5mV. An equivalent circuit incorporating ohmic internal resistance, interfacial film impedance, and charge transfer impedance was used for fitting, and the sum of the interfacial film impedance and charge transfer impedance was taken as the interfacial impedance.
[0078] The specific test results are shown in Table 2. The data in the table are the average values of the six cells in each group. The interface impedances of the experimental group and the control group after 100 cycles are 18.5mΩ and 35.2mΩ, respectively.
[0079] Table 2. Effects of different gel treatment methods on the activation process and interfacial impedance. Experimental group (with a stability threshold) 4.2 12 18.5 Control group (no stability threshold) 8.5 28 35.2 Table 2 shows that the maximum temperature rise during activation in the experimental group was 4.2℃ and the thickness change was 12μm, both lower than the 8.5℃ and 28μm of the control group; the interfacial impedance of the experimental group was also significantly lower after 100 cycles. Figure 3 As shown, SEM observations of the negative electrode surface at the same magnification after cycling revealed that the experimental group had a continuous film layer with fewer cracks, while the control group showed more cracks and localized peeling areas.
[0080] Combine Table 2 and Figure 3 It is known that controlled cooling, settling, and gel state assessment after deep polymerization can reduce the overlap between the residual thermal polymerization process and the electrochemical activation process, thereby reducing the temperature rise and thickness fluctuation during activation and facilitating the formation of a negative electrode interface film with a more continuous morphology and lower impedance after cycling.
[0081] Example 13 This embodiment aims to verify the impact of high-voltage access threshold on cell expansion trend and high-voltage interface stability. Twelve cells assembled in the same batch were selected and randomly divided into an experimental group and a control group, with six cells in each group.
[0082] The experimental group, following Example 1, completed the first formation at 40℃ and 0.10C, and then stood for 40 minutes. High-voltage access was assessed based on voltage drop, AC internal resistance change, thickness change, and temperature recovery time. Once the conditions were met, the cells were charged to 4.53V at 45℃ and 0.15C. The control group, after completing the first formation, did not perform interface buffering or state assessment; the ambient temperature was immediately raised to 45℃, and the cells were charged to 4.53V at 0.15C. During high-voltage formation, the cell center thickness was measured at 1-minute intervals for both groups, maintaining a clamping pressure of 5 kPa. The thickness before the target high-voltage formation was used as a baseline, and the increase in thickness was used to characterize cell expansion and gas generation trends. After formation and aging, both groups were stored at 60±2℃ for 7 days at a full charge of 4.53V, then restored to 25℃, and the 0.2C discharge capacity was tested.
[0083] like Figure 4 As shown, the thickness of the experimental group increased gradually after high-voltage formation, with a maximum increase of 0.18±0.04 mm; the control group showed a significant and rapid increase within the first 20 minutes after high-voltage formation, with a maximum increase of 0.52±0.11 mm. After 7 days of storage, the capacity retention rate was calculated as the ratio of the 0.2C discharge capacity after storage to the 0.2C discharge capacity before storage. The rate was 96.5%±0.7% for the experimental group and 91.2%±1.4% for the control group. The average thickness growth rate after storage was 1.4% for the experimental group and 3.5% for the control group.
[0084] Figure 4 The capacity data shows that setting an interface buffer after the first formation and only allowing cells that meet the requirements for voltage drop, internal resistance, thickness and temperature recovery to enter the target high-voltage formation can reduce the instantaneous expansion trend when switching directly from the low voltage stage to the high voltage stage. This allows the negative electrode interface film and the positive electrode high-potential interface film to have a more stable state before being subjected to 4.53V high voltage, thereby improving the capacity retention after high-voltage storage.
[0085] Example 14 This embodiment verifies the effect of the anomaly rollback mechanism on improving manufacturing yield. Statistics were collected from 10 consecutive trial production batches, each containing 100 cells, for a total of 1000 cells. Each batch was prepared according to the state detection and admission logic of Example 1, and the anomaly triggering stage, correction method, correction result, and final product judgment result were recorded.
[0086] Of the 1000 cells tested, 120 triggered anomaly warnings at at least one stage, accounting for 12.0%. Among these, 44 cells exhibited anomalies during the wetting stage, primarily due to insufficient total weight gain or excessively high AC internal resistance after wetting; 31 cells exhibited anomalies in the gel state after polymerization, primarily due to insufficient polymerization conversion or AC internal resistance exceeding the upper limit; 25 cells exhibited anomalies during the interface activation stage, primarily due to excessive temperature rise or thickness variation; and 20 cells exhibited anomalies in the high-voltage access after the first formation, primarily due to excessive voltage drop. After performing supplementary liquid injection or alternating vacuum-atmospheric pressure wetting, supplementary polymerization or hot wetting and resting, reducing activation current or pausing charging, extending the interface buffer or supplementing film formation with low current, 85 cells recovered to the corresponding access range, including 36 during the wetting stage, 20 during the polymerization stage, 17 during the activation stage, and 12 after the first formation; the remaining 35 cells were rejected because they still failed to meet the standards after two corrections or exhibited continuous gas production, abnormal temperature rise, and thickness increase. Ultimately, 965 finished cells were obtained, with a manufacturing yield of 96.5%. If all 120 warning cells are scrapped directly, the yield rate will be only 88.0%. Therefore, the abnormality correction path contributed 8.5 percentage points to the yield improvement. The disassembly and inspection of the screened cells also showed that their abnormality locations were consistent with the inadequate wetting, uneven gelation, or interfacial side reactions indicated by the corresponding state parameters.
[0087] The above statistics show that when the status parameters do not meet the admission conditions, the cells are not forcibly transferred or directly scrapped. Instead, a limited number of targeted corrections are performed based on the type of abnormality, and the process flow is only resumed after the retest is qualified. Cells that cannot be restored or have safety abnormalities are promptly screened out, which can reduce the risk of potential defects entering the high-voltage stage and the loss of repairable intermediate products.
[0088] This embodiment demonstrates that the abnormal rollback and screening mechanism can repair cells whose wetting, gelling, or interface states temporarily deviate from the target range into qualified finished products, and prevent unrepairable cells from entering the subsequent high-voltage process, thereby improving the manufacturing yield and material utilization of pure graphite negative electrode high-voltage gel lithium batteries.
[0089] Experimental results show that the pure graphite negative electrode high-voltage gel lithium battery prepared in this application can complete controlled activation, step formation and aging at a charging cutoff voltage of 4.45V and above, and exhibits low high-voltage storage thickness growth and AC internal resistance growth. It can be used in power supply scenarios with high requirements for energy density and safety, such as smartphones, drones, portable electronic devices and power batteries.
[0090] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A step preparation method of a pure graphite negative electrode high-voltage gel lithium battery, characterized in that, include: S1. The battery cell is assembled using a high-voltage positive electrode sheet, a pure graphite negative electrode sheet, and a porous diaphragm, and the battery cell is dried, injected with liquid in stages, and impregnated. S2. Obtain the wetting state parameters of the battery cell, and determine whether the battery cell meets the polymerization admission conditions based on the wetting state parameters. Only the battery cells that meet the polymerization admission conditions are subjected to prepolymerization, deep polymerization and cooling and standing to obtain gel battery cells. S3. Obtain the gel state parameters of the gel cell, determine whether the gel cell meets the activation admission conditions based on the gel state parameters, and only perform interface activation on the gel cells that meet the activation admission conditions. S4. Obtain the activation state parameters after interface activation, and determine whether the gel cell meets the formation admission conditions based on the activation state parameters. Only perform the first formation on the gel cells that meet the formation admission conditions. The cutoff voltage of the first formation is lower than the target high voltage cutoff voltage. S5. Perform interface buffering on the gel cell that has completed the first formation, obtain the interface state parameters after the first formation, determine whether the gel cell meets the high voltage access conditions based on the interface state parameters, and only perform target high voltage formation on the gel cell that meets the high voltage access conditions. The charging cutoff voltage of the target high voltage formation is not lower than 4.45V. S6. Aging the gel cell that has completed the target high-voltage formation, and determining the finished cell based on the state changes before and after aging. The wetting state parameter is used to characterize the degree of wetting of the electrolyte into the electrode pores and membrane channels; the gel state parameter is used to characterize the impedance and structural stability after polymerization; the activation state parameter is used to characterize the interfacial conductivity between the gel and the electrode; and the interface state parameter is used to characterize the stability of the electrode interface formed after the first formation.
2. The method of claim 1, wherein, The positive electrode active material of the high-voltage positive electrode sheet is high-voltage lithium cobalt oxide suitable for a charging cut-off voltage of not less than 4.45V; the negative electrode active material of the pure graphite negative electrode sheet is artificial graphite, natural graphite or a combination of the two, and the negative electrode active material does not contain silicon, silicon suboxide, silicon-carbon composite materials or tin-based negative electrode materials.
3. The method of claim 2, wherein, Drying the battery cell includes: The battery cell is pre-dried at 80–110°C for 4–12 hours. The pre-dried battery cells were subjected to deep vacuum drying for 12–60 hours at 105–130℃ and a vacuum degree not exceeding -0.095 MPa. The internal moisture content of the battery cell after deep vacuum drying is detected, and the battery cell is injected with electrolyte in stages when the internal moisture content is not higher than 100 ppm.
4. The method of claim 1, wherein, The stepwise injection and infiltration include: Determine the saturated liquid absorption capacity of the battery cell; A first electrolyte is injected into the battery cell. The first electrolyte includes a base high-voltage electrolyte, a polymer monomer, and an initiator. The amount of the first electrolyte injected is 60% to 85% of the saturated absorbent volume. The battery cell injected with the first electrolyte was vacuum-immersed for 30 to 120 minutes at 35–55°C and a vacuum degree not higher than -0.090 MPa. A second electrolyte is injected into the vacuum-impregnated cell. The second electrolyte is either a basic high-voltage electrolyte or an electrolyte with a lower content of polymer monomers than the first electrolyte. The amount of the second electrolyte injected is 15% to 40% of the saturated liquid absorption capacity. After the second injection of electrolyte is completed, let the battery cell stand for 5 to 60 minutes.
5. The method according to claim 4, characterized in that, The immersion state parameters include the total weight gain of the battery cell, the pressure change at the end of vacuum immersion, the AC internal resistance before and after immersion, and the AC internal resistance change rate during the standing process after the second liquid injection. The aggregation admission conditions include: The total increase in the weight of the battery cell is within the target total injection volume range of the first electrolyte and the second electrolyte; The pressure change between two adjacent detection cycles at the end of the vacuum immersion period shall not exceed the upper limit of the pressure change. The internal resistance of AC after immersion is lower than that at the initial stage of immersion. The rate of change of AC internal resistance during the settling process does not exceed the upper limit of the rate of change of internal resistance.
6. The method according to claim 1, characterized in that, The prepolymerization, deep polymerization, and cooling and settling process includes: The battery cell is prepolymerized at 50–65°C for 1–4 hours; Deep polymerization is carried out by heating to 65-80℃ at a heating rate of 0.5-3℃ / min. The temperature of deep polymerization is 5-20℃ higher than the temperature of prepolymerization. The deeply polymerized battery cells are cooled to 20-30°C at a cooling rate of 2-10°C / h and left to stand for 0.5-6 hours. The gel state parameters include AC internal resistance, open circuit voltage, and cell thickness at the beginning and end of the settling period. The activation admission conditions include that the AC internal resistance at the end of the settling period is not higher than the upper limit of the gel internal resistance, the AC internal resistance change rate during the settling process is not higher than the upper limit of the gel internal resistance change rate, the open circuit voltage change is not higher than the upper limit of the voltage change, and the cell thickness change is not higher than the upper limit of the thickness change.
7. The method according to claim 1, characterized in that, The interface activation includes first interface activation and second interface activation; The first interface is activated at 25–35°C with a current of 0.02C–0.08C for 0.5–3 hours. When the AC internal resistance after the first interface activation is lower than the AC internal resistance before the first interface activation, and the maximum temperature rise and cell thickness change during the first interface activation process are not higher than the corresponding upper limits, the second interface activation is performed. The second interface activation is carried out at 32-40°C with a current of 0.06C-0.12C, and the temperature and current of the second interface activation are higher than those of the first interface activation, respectively. After the second interface activation is completed, the cell is left to stand for 5 to 60 minutes. The activation state parameters include the voltage drop before and after standing, the change in AC internal resistance before and after the second interface activation, the maximum temperature rise during the interface activation process, and the change in cell thickness.
8. The method according to claim 1, characterized in that, The first formation is performed at 35–45°C with a current of 0.08C–0.20C, and the cutoff voltage of the first formation is 4.15–4.35V; The interface buffering includes stopping charging after the first formation is completed and letting it stand at 35-45°C for 10-120 minutes. The interface state parameters include the voltage drop during the interface buffering process, the change in AC internal resistance before and after the first formation, the change in cell thickness, and the cell temperature recovery time. The high-voltage access conditions include that the voltage drop, AC internal resistance change, and cell thickness change are not higher than their respective upper limits, and the cell temperature recovers to the target temperature range within a set recovery time. The target high voltage formation is carried out at 40-50°C with a current of 0.10C-0.30C to 4.45-4.55V, and after reaching the target high voltage cutoff voltage, constant voltage charging is performed until the charging current drops to 0.01C-0.05C.
9. The method according to claim 1, characterized in that, If the state parameters at any stage do not meet the corresponding admission conditions, the following procedure shall be followed: When the total increase in cell weight is less than the target total electrolyte injection volume, replenish electrolyte; When the total weight gain of the battery cell is within the target total liquid injection volume range, but the AC internal resistance after immersion is higher than the upper limit of the immersion internal resistance, extend the vacuum immersion time or perform alternating immersion under vacuum and normal pressure. When the polymerization conversion rate of the gel cell is lower than the lower limit of conversion rate, supplementary polymerization is carried out; when the AC internal resistance of the gel cell is higher than the upper limit of gel internal resistance and the change in cell thickness is not higher than the corresponding upper limit, hot soaking and standing are carried out at 35-50℃. When the maximum temperature rise or cell thickness change during the interface activation process exceeds the corresponding upper limit, reduce the interface activation current or suspend charging. When the voltage drop after the first formation is higher than the corresponding upper limit, while the change in AC internal resistance and the change in cell thickness are not higher than the corresponding upper limit, the interface buffer time is extended, or a current lower than the first formation current is used for supplementary film formation. When the battery cell produces gas, or when either the maximum temperature rise or the thickness change exceeds the upper limit for anomaly detection, the battery cell will be stopped from proceeding to the next manufacturing stage.
10. The method according to claim 1, characterized in that, The aging process includes placing the gel cell that has completed the target high-voltage formation at 35–50°C for 12–48 hours. The changes in state before and after aging include the decrease in open-circuit voltage, the increase in AC internal resistance, the increase in cell thickness, and self-discharge parameters. When the open-circuit voltage drop, AC internal resistance growth rate, and cell thickness growth rate are not higher than the corresponding finished product judgment upper limit, and the cell does not bulge, leak, or produce gas, the cell is determined to be a finished cell. When the cell does not exhibit bulging, leakage, or gas generation, but the AC internal resistance growth rate or open-circuit voltage drop exceeds the corresponding finished product judgment limit, the state change is obtained again after extending the aging time.